2003
DOI: 10.1067/mva.2003.56
|View full text |Cite
|
Sign up to set email alerts
|

High-risk carotid endarterectomy: Fact or fiction

Abstract: The concept of the high-risk CEA must be critically reexamined. Although 29% of patients for CEA were high risk as defined by others, we found no evidence that this influenced the results after CEA. Patients with significant medical comorbidities, contralateral carotid occlusion, and high carotid lesions can undergo operation without increased complications. If a high-risk group exists, it is small and restricted to reoperation or radiated neck (4% in this series). With this possible exception, carotid angiopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 32 publications
(28 reference statements)
4
90
0
3
Order By: Relevance
“…Kragsterman et al (16) confirmed this association in a Swedish cohort (risk ratio 1.41, P = 0.02), whereas Rothwell et al (28) demonstrated, in a meta-analysis of available literature, that age greater than 75 years confers a 36% increase in the risk of stroke or death owing to CEA. Although the concept of a high-risk CEA population remains controversial (6,21,26), our findings raise the possibility that post-CEA stroke and neurocognitive decline share related risk factors and etiologies.…”
Section: Discussionmentioning
confidence: 85%
“…Kragsterman et al (16) confirmed this association in a Swedish cohort (risk ratio 1.41, P = 0.02), whereas Rothwell et al (28) demonstrated, in a meta-analysis of available literature, that age greater than 75 years confers a 36% increase in the risk of stroke or death owing to CEA. Although the concept of a high-risk CEA population remains controversial (6,21,26), our findings raise the possibility that post-CEA stroke and neurocognitive decline share related risk factors and etiologies.…”
Section: Discussionmentioning
confidence: 85%
“…They have demonstrated surgical results that are much different from what is observed in other reference services, as well as from the results of general experience with patients at Medicare (Table 5). [11][12][13]56,60,63 By acting like that, the studies SAPPHIRE and SPACE showed very similar results, certainly due to reasons explained above. 11,13 The EVA-3S study, funded by the French Department of Health and performed in university centers, showed extremely favorable results regarding endarterectomy (3.9% in the CEA group and 9.6% in the CAS group), the reason why the ethics committee determined its suspension, since the evidence had already been confirmed.…”
Section: Limitations Of the Endovascular Techniquementioning
confidence: 78%
“…In anatomic risk, they included 66 patients with contralateral occlusion, 29 cases of reoperations, three patients with previous radiotherapy and 53 with distal lesion. 60 Those authors possibly published the best study to demonstrate the mystification created with the widespread use of the "high risk" classification. They were careful enough to offer the 560 low-risk patients the same cares provided to the group of 228 high-risk patient, namely patch in 86 and 84% of cases, internal shunt in 93 and 97% of cases and general anesthesia in 98% of cases.…”
Section: High-risk Patients For Carotid Endarterectomymentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 However, larger studies such as an analysis of 13 622 CEA operations in the National Surgical Quality Improvement Program have found higher periprocedure complication rates in patients with SAPPHIRE high-risk features (3.0% mortality in high risk versus 1.7% without high risk, P<0.001).…”
Section: Discussionmentioning
confidence: 99%